2016
DOI: 10.1016/j.bbrep.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Lack of mycothiol and ergothioneine induces different protective mechanisms in Mycobacterium smegmatis

Abstract: Mycobacterium smegmatis contains the low molecular weight thiols, mycothiol (MSH) and ergothioneine (ESH). Examination of transposon mutants disrupted in mshC and egtA, involved in the biosynthesis of MSH and ESH respectively, demonstrated that both mutants were sensitive to oxidative, alkylating, and metal stress. However, the mshC mutant exhibited significantly more protein carbonylation and lipid peroxidation than wildtype, while the egtA mutant had less protein and lipid damage than wildtype. We further sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
1
14
1
Order By: Relevance
“…This could reflect the predominant role of GSH in this gram-negative genus because we found that GSH is indeed made in much higher quantities than EGT is under all conditions tested. Furthermore, we do not see crosstalk between the EGT and GSH pathways in Burkholderia species, unlike that found in Mycobacterium species, in which a mycothiol mutant showed significantly increased EGT production, and mycothiol and EGT are both shown to be important for protection against oxidative stress (7,8). Burkholderia species are predominantly saprophytic organisms, and in a way, their lifestyles could be more closely related to fungi than to mycobacteria.…”
Section: Discussioncontrasting
confidence: 59%
“…This could reflect the predominant role of GSH in this gram-negative genus because we found that GSH is indeed made in much higher quantities than EGT is under all conditions tested. Furthermore, we do not see crosstalk between the EGT and GSH pathways in Burkholderia species, unlike that found in Mycobacterium species, in which a mycothiol mutant showed significantly increased EGT production, and mycothiol and EGT are both shown to be important for protection against oxidative stress (7,8). Burkholderia species are predominantly saprophytic organisms, and in a way, their lifestyles could be more closely related to fungi than to mycobacteria.…”
Section: Discussioncontrasting
confidence: 59%
“…7 ). The sensitivity to all of these agents was reversed in the complemented strain demonstrating the importance of EGT in M. smegmatis ( 61 ).…”
Section: Ergothioneine In Mycobacteriamentioning
confidence: 96%
“…Singh et al reported that the transposon mutant of egtA in M. smegmatis did not produce EGT; however, there is no difference in growth compared with the wild type ( 61 ). The egtA mutant, R119, was shown to be highly susceptible to oxidative agents such as cumene hydroperoxide and diamide; alkylating agents such as N-ethylmalemide, iodoacetamide, and chlorodinitrobenzene; and metals such as Cd 2+ , Cu 2+ , SeO 3 2− , TeO 3 2− , and CrO 4 2− ( Fig.…”
Section: Ergothioneine In Mycobacteriamentioning
confidence: 99%
See 2 more Smart Citations